Analyzing the Performance of Rumah Zakat in Distributing Ziswaf Funds: A Study in Kediri City, East Java - Adin Fadilah; Mirahayu Mirahayu (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
In the current pandemic period, Islamic Philanthropy (ZISWAF) should be able to provide a solution to the problems of the ummah. For this reason, in order to optimize the distribution and distribution of zakat at Rumah Zakat in the city of Kediri, both in the field of utilization and benefits, appropriate strategies are needed to overcome problems during the current pandemic that is happening. From the background of these problems, good strategies are needed in terms of distribution and distribution as well as education is also needed to the surrounding community. Based on the description above, it is necessary to conduct research to further examine how good the distribution, distribution strategies, and ways to make the public know more about the obligation to pay zakat, give infaq, or shadaqah at the National Amil Zakat Agency. This was field research. The findings of this research were that the Rumah Zakat raises funds directly starting from the members of the Rumah Zakat itself, inviting several communities and donors who come to the Rumah Zakat to give their funds, while indirectly it was carried out through social media. In the activities of distributing zakat, alms, infaq and waqf, Rumah Zakat Kediri had consumptive and productive programs. Rumah Zakat’s performance in optimizing the distribution of ziswaf funds to mustahik was carried out through the Empowered Village program and other programs.